Assessment of the binder blending in bituminous mixtures based on the development of an innovative sustainable infrared imaging methodology. (1st April 2019) - Vassaux, S.; Gaudefroy, V.; Boulangé, L.; Pévère, A.; Michelet, A.; Barragan-Montero, V.; Mouillet, V.
Abstract: Reclaimed Asphalt (RA) is more and more used in the road recycling industry because it allows reducing the consumption in non-renewable raw materials such as virgin bitumen which comes from the petroleum distillation. As bitumen is oxidation-sensitive, some technical issues are however raised about the mix design and the binder blending between the aged and virgin binders. Particularly, the question lies on the ability of the virgin binder to mix with the RA aged binder to form a homogeneous product in defined manufacturing conditions. To answer this question, most of road studies extract with a chlorinated solvent the total bituminous binder from the asphalt mixture to characterize then oxidation or rheological properties. However, this solvent extraction technique is based on a complete binder dissolution which may alter physicochemical properties of the mixture. The objective is also to develop a solvent-free and non-destructive methodology to in situ assess the binder blending in manufactured mixtures. Using infrared imaging ATR microscopy, homogeneity is defined from spatial distributions in carbonyl functions and the methodology is developed on modeled binder mixtures. The influence of the aged binder temperature and mixing time is then investigated on the binder blending. Results show that high and close temperatures between binders are necessary but not sufficient to obtain a homogeneous mixture whereas a longer mixing time improves the binder blending. The developed chemomap methodology also allows demonstrating the influence of manufacturing process parameters on the binder blending in road asphalt mixtures. At the binder scale, the present work constitutes an interesting, rapid and economical approach to optimize the manufacturing parameters of the asphalt mixture design. The innovative infrared imaging methodology also opens perspectives to gain a better knowledge about molecular distributions and homogeneity of any hydrocarbon mixture which constitutes an essential criterion for the performance of more sustainable materials. Graphical abstract: Homogeneity assessment in binder mixtures using the combination of a novel solvent-free infrared methodology and the statistical treatment of carbonyl spatial distributions.Image 10032620 Highlights: A solvent-free chemomap methodology is developed to assess the binder blending. Homogeneity of bituminous mixtures is defined from carbonyl spatial distributions. Chemomap helps optimizing manufacturing process parameters of recycled materials. High and close binder temperatures are necessary to obtain a homogeneous mixture. A longer mechanical mixing time guarantees a more efficient binder blending.